Rupture of hernial sac in an infant following peritoneal dialysis. - Sackey, A.H.; Cook, R.C.M.; Judd, B.A. (Peritoneal Dialysis International, 1994)
Inguinal hernais are a well-known compilation of Continuous Ambulatory Peritoneal dialysis (CAPD), with an estimated incidence of 15% in Children (1). We describe an infant with an unusual presentation.
Keywords: Hernial sac; Infant; Peritoneal Dialysis